Lipid antigens in bile from patients with chronic liver diseases activate natural killer T cells. (16th November 2020) - Valestrand, L.; Berntsen, N. L.; Zheng, F.; Schrumpf, E.; Hansen, S. H.; Karlsen, T. H.; Blumberg, R. S.; Hov, J. R.; Jiang, X.; Melum, E.
Summary: Natural killer T (NKT) cells are an abundant subset of liver lymphocytes activated by lipid antigens presented on CD1d molecules that are expressed by cholangiocytes. We aimed to determine if bile from patients with chronic liver diseases contains antigenic lipids that can activate NKT cells. Using murine invariant (24.7, 24.8 and DN32.D3) and non‐invariant (14S.6, 14S.7 and 14S.10) NKT hybridomas we investigated the presence of lipid antigens in bile collected from the gallbladder of patients undergoing liver transplantation due to end‐stage liver disease. Biliary microbiota profiles were generated using 16S rRNA amplicon sequencing. We found that the patient bile samples contain antigens that activate both invariant and non‐invariant NKT hybridomas (24.7, 24.8, DN32.D3, 14S.6, 14S.7 and 14S.10), as demonstrated by activation of at least one hybridoma by eight of 10 bile samples. Activation at high dilutions suggests that some antigens are highly potent. We used the non‐invariant NKT hybridoma 14S.6 to screen 21 additional patient bile samples for NKT‐reactivity and demonstrated that 12 of 21 bile samples resulted in activation, three of which gave a strong activation. Four of 12 activating bile samples contained microbial DNA. Our results reveal an immunological pathway that could be of critical importance in biliary immunology. Abstract : Bile from patients with chronic liver diseases contains antigens that activate natural killer T cells, an important subgroup of liver lymphocytes . Activation of this immunological pathway suggests that bile antigens may be important in inflammatory bile duct diseases.